2012
DOI: 10.2136/sssaj2011.0113
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Availability in an Oxisol Amended with Biosolids in a Long-Term Field Experiment

Abstract: Many extractors are used to quantify available P in soils, but few studies have assessed the availability of P in soils of the wet tropics amended with high rates of biosolids. In this study, ion exchange resin, Mehlich-1 solution, and Fe-impregnated strips were used to quantify available P in samples from an Oxisol amended with surface-applied biosolids in a long-term field experiment. The soil's maximum capacity for P adsorption was also estimated. Experimental design consisted of randomized blocks, with fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
4
1
Order By: Relevance
“…Although some studies have found that Al plays a more significant role than Fe in P sorption mechanics for both temperate soils (Lopez-Hernandez and Burnham 1974;Sakadevan and Bavor 1998;Börling et al 2001) and tropical soils (Fontes and Weed 1996;Poudel and West 1999;Hartono et al 2005;Gichangi et al 2008;Alleoni et al 2012;Chimdi et al 2013;de Campos et al 2016), our study found that DCB-extracted Al-and Fe-oxides were similarly correlated with the P Qmax values (r = 0.470 and 0.461 respectively). Considering the low R 2 values for these parameters in describing P Qmax, this lack of discrepancy in parameter influence is not surprising.…”
Section: Soil Researchcontrasting
confidence: 54%
See 2 more Smart Citations
“…Although some studies have found that Al plays a more significant role than Fe in P sorption mechanics for both temperate soils (Lopez-Hernandez and Burnham 1974;Sakadevan and Bavor 1998;Börling et al 2001) and tropical soils (Fontes and Weed 1996;Poudel and West 1999;Hartono et al 2005;Gichangi et al 2008;Alleoni et al 2012;Chimdi et al 2013;de Campos et al 2016), our study found that DCB-extracted Al-and Fe-oxides were similarly correlated with the P Qmax values (r = 0.470 and 0.461 respectively). Considering the low R 2 values for these parameters in describing P Qmax, this lack of discrepancy in parameter influence is not surprising.…”
Section: Soil Researchcontrasting
confidence: 54%
“…The high weathering rate of tropical soils leads to an abundance of clay minerals, providing a high surface area and numerous binding sites (McGechan and Lewis 2002). For ESMs, this provides evidence that information about clay content could significantly aid in the estimation of P sorption parameters for tropical soils (Lopez-Hernandez and Burnham 1974;McGroddy et al 2008;Bruland and DeMent 2009;Moazed et al 2010;Alleoni et al 2012). Although P sorption isotherms are not often performed in routine soil analyses, particle size is a frequently measured parameter.…”
Section: Soil Researchmentioning
confidence: 98%
See 1 more Smart Citation
“…This characterizes the kinetic relationship between the labile and stable pools. The vdZ‐vR model was successfully applied to the Brazilian tropical soils similar to those of SSA (Alleoni et al, ; de Campos et al, ), across a range of pH‐values (Andersson et al, ; do Carmo Horta et al, ; do Carmo Horta & Torrent, ; Freese et al, ; House et al, ; Maguire et al, ); all of which were within the range of SSA soils (Hengl et al, ). vdZ‐vR (Freese et al, ; van der Zee & van Riemsdijk, ) states that the concentration of the stable pool controlled by the chemical kinetics ( S c , kg · ha −1 ) is proportional to the size of weathered (amorphous, oxalate‐extractable) Fe and Al oxide concentrations and the size of the labile pool.…”
Section: Methodsmentioning
confidence: 99%
“…The optimum pH for P availability to crops in the soil is between 6 and 7 [75]. Lowering soil pH (4.5-5.1) causes decreased soil microbial activities and can lead to subsequent changes in the substrate utilization [76,77].…”
Section: Phmentioning
confidence: 99%